Direct 17O MRI with partial volume correction: first experiences in a glioblastoma patient - Hoffmann, Stefan Heinrich; Radbruch, Alexander; Bock, Michael; Nagel, Armin Michael (Magnetic resonance materials in physics, biology and medicine, 2014)
In tumor cells the energy production is shifted from aerobic to anaerobic metabolization of glucose, which makes the cerebral metabolic rate of oxygen consumption (CMRO2) a diagnostic parameter for tissue viability. Direct oxygen-17 (17O) MRI during inhalation of 17O gas allows for a non-invasive determination of the CMRO2. However, the low spatial resolution and the fast transverse relaxation of 17O lead to partial volume effects that severely bias the quantification of signal intensities. The aim of this work was to determine the CMRO2 in a tumor patient by 17O MRI in combination with a partial volume correction (PVC) scheme.
Gesehen am 21.10.2020
Im Titel ist die Zahl "17" hochgestellt